Systematic review on consumer forgiveness: Clarifying the domain and future research agenda - Özdemir, Neslişah (ACC Publishing, 2023)
Consumer forgiveness has gained prominence in marketing literature, particularly in investigating service failure and recovery. In this vein, this study aims to systematically review the consumer forgiveness literature and provide valuable suggestions for future research endeavours based on the discovered gaps in the existing literature. The present study thoroughly examined 77 peer-reviewed journal articles on consumer forgiveness from the Scopus database. The findings are discussed under the headings of descriptive overview (year and journal) and content analysis that consists of theoretical background, methodological trends (research design, data collection method, sample size, industry, analysis techniques, measurement) and thematic issues (antecedents, consequences, mediators and moderators) subtitles. This study contributes to the body of knowledge by clarifying the literature on consumer forgiveness, identifying gaps, and making suggestions for future research. This study also contributes to the literature by proposing a comprehensive framework that aligns with the variables investigated in previous research on consumer forgiveness.